Leaders or laggards? The evolution of electric utilities' business portfolios during the energy transition. (September 2018) - Frei, Fanny; Sinsel, Simon R.; Hanafy, Ahmed; Hoppmann, Joern
Abstract: Effectively mitigating climate change requires a fundamental and rapid transition in the way electricity is generated and used. The global electricity sector, however, is still dominated by large incumbent utility companies, which have historically been slow to embrace change. Given this seeming contradiction, in this paper we investigate whether and how 25 of the biggest electric utilities worldwide have adapted their business portfolios during the energy transition from 2003 to 2015. We observe three developments in utilities' business portfolios, namely an increase in (1) de-carbonization, (2) decentralization and servitization, and (3) system integration and balancing. Our results indicate that utilities have been more proactive in embracing de-carbonization as the core goal of the energy transition than the two successive challenges of decentralization and system integration. The lag in system integration is surprising, given that utilities traditionally possess considerable knowledge and assets that they could leverage to integrate decentralized low-carbon generation. We conclude that utilities can play a major role in integrating and balancing the components of a low-carbon electricity system, but that regulatory changes or additional policy incentives may be necessary to spur system integration as a critical part of the energy transition. Highlights: We track the business portfolios of the world's largest utilities from 2003 to 2015. We identify three main developments in line with the energy transition. Developments include de-carbonization, decentralization, and system integration. Utilities do not focus on activities closest to their traditional business mandate. Changes in policy incentives and regulation may be needed to spur such activities.